A BRITES DE JÚLIA NERY: UMA POSSIBILIDADE TRANSGRESSORA EM MEIO AO DISCURSO FICCIONAL - Machado, Alleid Ribeiro (Revista Desassossego, 2009)
This paper makes a lecture of Crônica de Brites, by Júlia Nery. The lecture is based on the concept of gender and performance, where the gender is built, as the basal assumption. Merging any analysis of the romance excerpts and gender theories, we show how the author builds a critical and transgressive essay. The author makes a dialogue with the historical past of Portugal through the personage of Brites de Almeida which reveals some mechanisms that yield the subjects in fixed and “naturally” immutable realities.